Trophobiosis between a new species of Williamsrhizoecus (Hemiptera: Coccomorpha: Rhizoecidae) and Acropyga silvestrii (Hymenoptera: Formicidae) in Tanzania - Schneider, Scott A.; Lapolla, John S. (Zootaxa, 2020)
A new myrmecophilous species of root mealybug, Williamsrhizoecus udzungwensis sp. n., is described from individuals found living within a nest of Acropyga silvestrii in the Udzungwa Mountains of Tanzania. Acropyga ants are highly specialized, obligate associates of scale insects, typically members of the scale family Xenococcidae. Acropyga are best known for vertically transmitting trophobiotic partners during their nuptial flights and for housing them within brood chambers. This article presents the first record of trophobiosis between a species of Williamsrhizoecus and Acropyga, and only the second record of an association between Acropyga and rhizoecids in the Old World. This discovery contributes important information about the few species of Rhizoecidae confirmed to engage in these unique symbioses, each putatively the result of a past horizontal transmission event from a xenococcid to a rhizoecid lineage. Included is a discussion on the diagnosis of Williamsrhizoecus and an updated key to the species.